Transgenerational epigenetic inheritance in birds. Issue 2 (26th April 2018) - Guerrero-Bosagna, Carlos; Morisson, Mireille; Liaubet, Laurence; Rodenburg, T Bas; de Haas, Elske N; Košťál, Ľubor; Pitel, Frédérique
Abstract: While it has been shown that epigenetics accounts for a portion of the variability of complex traits linked to interactions with the environment, the real contribution of epigenetics to phenotypic variation remains to be assessed. In recent years, a growing number of studies have revealed that epigenetic modifications can be transmitted across generations in several animal species. Numerous studies have demonstrated inter- or multi-generational effects of changing environment in birds, but very few studies have been published showing epigenetic transgenerational inheritance in these species. In this review, we mention work conducted in parent-to-offspring transmission analyses in bird species, with a focus on the impact of early stressors on behaviour. We then present recent advances in transgenerational epigenetics in birds, which involve germline linked non-Mendelian inheritance, underline the advantages and drawbacks of working on birds in this field and comment on future directions of transgenerational studies in bird species.